Two AT‐Hook proteins regulate A/NINV7 expression to modulate sucrose catabolism for cold tolerance in Poncirus trifoliata. Issue 6 (9th July 2022) - Dahro, Bachar; Wang, Yue; Khan, Madiha; Zhang, Yang; Fang, Tian; Ming, Ruhong; Li, Chunlong; Liu, Ji‐Hong
Summary: Invertase (INV)‐mediated sucrose (Suc) hydrolysis, leading to the irreversible production of glucose (Glc) and fructose (Frc), plays an essential role in abiotic stress tolerance of plants. However, the regulatory network associated with the Suc catabolism in response to cold environment remains largely elusive. Herein, the cold‐induced alkaline/neutral INV gene PtrA/NINV7 of trifoliate orange ( Poncirus trifoliata (L.) Raf.) was shown to function in cold tolerance via mediating the Suc hydrolysis. Meanwhile, a nuclear matrix‐associated region containing A/T‐rich sequences within its promoter was indispensable for the cold induction of PtrA/NINV7 . Two AT‐Hook Motif Containing Nuclear Localized (AHL) proteins, PtrAHL14 and PtrAHL17, were identified as upstream transcriptional activators of PtrA/NINV7 by interacting with the A/T‐rich motifs. PtrAHL14 and PtrAHL17 function positively in the cold tolerance by modulating PtrA/NINV7 ‐mediated Suc catabolism. Furthermore, both PtrAHL14 and PtrAHL17 could form homo‑ and heterodimers between each other, and interacted with two histone acetyltransferases (HATs), GCN5 and TAF1, leading to elevated histone3 acetylation level under the cold stress. Taken together, our findings unraveled a new cold‐responsive signaling module (AHL14/17‐HATs‐ A/NINV7 ) for orchestration of Suc catabolism and cold tolerance, which shed light on the molecular mechanisms underlying Suc catabolism catalyzed by A/NINVs under cold stress.